TELAAH KONSEP DISTRIBUSI KEKAYAAAN PERSEPEKTIF EKONOMI ISLAM - Usman Zainuddin Urif1,Mahillatul Iffa Nu Silvia Maula Aulia3 (UIN Mataram, 2019)
This study aims to determine the property distribution in Islamic economic perspectives with the certainty that Islamic economics contains distribution concept with values of justice, norms and morals so that they are considered in accordance with Muslims personality. Research approach is library research with philosophical and phenomenological approach. A philosophical approach is used to look deeply at material philosophical objects such as values, principles, goals of Islamic economics and the concept of distribution. While the phenomenological approach is used to look for economic development both illustrated in society through poverty data statistical, as well as contained in a literature work such as books, documents, scientific works and research. Research result show that Islamic economic system aim is to improve the welfare of society and realize maqasid as sharia, and uphold the value of justice, so that at the level of distribution which is an important foundation is the guidance of Allah in QS. [59]: 7